Implementation of the asthma practice guideline in the Army Medical Department : evaluation of process and effects - Farley, Donna O.; Cretin, Shan.; Vernez, Georges; Pieklik, Suzanne; Dydek, George J.; Quiter, Elaine S.; Ashwood, J. Scott; Tu, Wenli; Arroyo Center; Center for Military Health Policy Research; Rand Corporation; United States. Army. (Santa Monica, CA : RAND, 2005)
In partnership with the Army Medical Department (AMEDD), RAND researchers worked to implement clinical practice guidelines in treatment of three common ailments (asthma, diabetes, and low back pain). This report is an evaluation of the asthma practice guideline demonstration. It documents the extent to which intended actions were implemented, assesses short-term effects on clinical practices, and measures the quality and limitations of available data for monitoring practice improvements and clinical outcomes. The authors found that, although the implementation scored some notable successes, resource limitations and organizational barriers curbed overall progress. They conclude that allowing for flexibility, monitoring the facilities consistently, and training providers thoroughly are the keys to implementing the practice guidelines throughout AMEDD. The also concluded that patient education was an area in need of improvement.
Introduction -- Introduction -- Asthma Populations and Practices at the Baseline -- The Guideline Implementation Process -- Effects of Guideline Implementation -- Synthesis of Findings from the Demonstration.
"Center for Military Health Policy Research."
"RAND Arroyo Center."
Includes bibliographical references (p. 173-176).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Army Medical Department; United States. -- Army -- Medical care -- Standards; Asthma -- Treatment -- United States -- Evaluation; Soldiers -- Medical care -- United States